Role of oxygen functionalities on the synthesis of photocatalytically active graphene-TiO2 composites - Luisa M. Pastrana-Martínez (2014)
Photocatalysis has gained relevance in many applications, including production of fuels, green synthesis of added value products and water detoxification. Graphene-TiO2 photocatalysts are attracting great attention, but they should be prepared adequately, protecting the carbon material from the surrounding reactive media, maximizing the contact between TiO2 and graphene, and envisaging broad spectral response. Hereby, graphene oxide was chemically reduced using vitamin C and glucose (environmental friendly reducing agents) as well as hydrazine, and the evolution of the graphene oxygenated surface groups was systematically analyzed (pH(PZC),TPD,TG, XPS, DRUV-Vis, Raman and ATR-FTIR). These functionalities (such as epoxy and hydroxyl groups) mediate the efficient and uniform assembly of the TiO2 nanoparticles on the graphene oxide sheets, leading to highly efficient photocatalysts both under near-UV/Vis and visible light, which is of particular relevance for solar applications.